Parents’ Perspectives on Stressors and Resources: Well-being and Social Support During Early Childhood Transitions - Pölzl-Stefanec, Eva; Gutmann, Nina (Revija za elementarno izobraževanje, 2025)
The transition from familial to institutional early childhood education and care (ECEC) settings is a critical phase for both children and parents. In this study, we examined the stressors and resources affecting parents during nursery and kindergarten settling-in processes. Using Antonovsky’s concept of coherence as the theoretical framework, we conducted fifteen qualitative semi-structured interviews with parents and analysed the emotional, organisational, and social challenges they perceived as stressors and resources during the transition phase. The findings showed that a resource-oriented approach can reduce stress and support the emotional and social adjustment of both parents and children.
Keywords: transition from home to ECEC setting, nursery and kindergarten settling-in, parental perspective, stressors and resources, sense of coherence.